BISMUTH MINERALS FROM YUGO-KONEVO AND POROKHOVSKOE TUNGSTEN DEPOSITS (SOUTH URALS) - A.V. Kasatkin; E.V. Belogub; A.M. Kuznetsov; K.A.Novoselov; R. Škoda; F. Nestola; D.A. Rogov (Минералогия)
A mineral assemblage including sulfosalts of the bismuthinite-aikinite (aikinite, bismuthinite, gladite, salzburgite, krupkaite, lindströmite, pekoite, friedrichite, hammarite), pavonite (makovickyite, cupromakovickyite, pavonite, dantopaite, mummeite), cupropavonite (cupromakopavonite, cupropavonite) and lillianite (lillianite s.s.) homologous series, as well as ángelaite, berryite, matildite, baksanite, ikunolite, tetradymite, hedleyite and native bismuth is identified in veinlet ores of the Yugo-Konevo and Porokhovskoe tungsten deposits (Chelyabinsk oblast, South Urals). The Bi minerals occur as individual grains or intergrowths in fluorite-muscovite-quartz veins with hübnerite and scheelite , inclusions in quartz and intersticial aggregates between pyrite, sphalerite and galena. Ángelaite, dantopaite, cupromakovickyite and cupromakopavonite are first found at the territory of Russian Federation and salzburgite, cupropavonite, makovickyite and mummeite are found for the first time in the South Urals.